Implementasi Total Quality Management pada Pendidikan Islam - Abidin, Zainal (Adabuna : Jurnal Pemikiran dan Pendidikan, 2022)
Total Quality Management is a concept of managing educational institutions in order to improve the quality of educational institutions with continuous and client-focused improvement efforts and total involvement in the implementation of Total Quality Management in educational institutions cannot be separated from all existing components such as school principals, teachers. Mas staff and support from external parties such as the school committee to work together to provide maximum service to students. This research method is a type of library research. The point of library research is research conducted by collecting data, information and various other types of data contained in the literature. The results of this study are that the implementation of Total Quality Management will not succeed in humans but needs a systematic process. The point of implementing Total Quality Management is reflected in the gradual and continuous process of improving quality by meeting customer or client expectations both internally and externally.